The Thai Folk Game "Jik Sen" has Become a Recreational Sport for Older People in Senior Citizen Schools - Tachapon Tongterm; Khanittha Chimphali; Metawut Pongthanu; Thanyaporn Pengseesang; Jeeranan Kaewma; Sarocha Namboonlue (OVS LLC, 2024)
Objectives. The purposes of this study were to: 1) develop an exercise program incorporating the Thai recreational sport "Jik Sen" for older people in senior citizen schools; 2) investigate the effects of the exercise program incorporating the Thai recreational sport "Jik Sen" on the physical fitness of older people in senior citizen schools; and 3) assess the satisfaction level of older people with the exercise program incorporating the Thai recreational sport "Jik Sen". Materials and methods. This was a two-group experimental study including the experimental group of 17 people (65.53 ± 3.43 years) and the control group of 17 people (65.76 ± 3.60 years). The participants in this study were healthy individuals aged 60 years and above, who were actively engaged in the elderly school program. They were selected using a purposive sampling method and subsequently assigned them to the experimental and control groups using a matching method based on BMI. The research tools consisted of the exercise program, which incorporated the Thai recreational sport "Jik Sen" developed by the research team, and the Senior Fitness Test (SFT). For a period of 8 weeks, the experimental group involved in an exercise regimen comprising 60 minutes of daily training in the Thai recreational sport "Jik Sen", with a frequency of 3 days per week. The control group was instructed to maintain their normal daily routine and did not participate in any physical activities or exercise programs during the experiment. The data were analyzed using mean, standard deviation, percentage, and t-test.  Results. 1) The exercise program incorporating the Thai recreational sport "Jik Sen" for older people in senior citizen schools can be appropriately used to promote exercise and sports in elderly schools in Thailand. The IOC value was 0.97. 2) A significant difference was observed in the mean scores of the 8-foot up-and-go test between the pre-experimental (mean = 7.94, S.D. = 1.34) and post-experimental (after 8 weeks) (mean = 6.70, S.D.= 0.79) periods for the experimental group at the level of 0.05. The mean scores of the 8-foot up-and-go test between the control group (mean = 7.84, S.D. = 1.16) and the experimental group (mean = 6.70, S.D. = 0.79) were also found to be significantly different at the level of 0.05. 3) The experimental group expressed high levels of satisfaction with the exercise program involving the Thai recreational sport "Jik Sen" for older people in senior citizen schools, with a mean score of 4.62 ± 0.51 points.    Conclusion. The exercise program incorporating the Thai recreational sport "Jik Sen" can effectively enhance the dynamic balance of older individuals in senior citizen schools. Furthermore, it has been shown to facilitate social interaction, improve cognitive abilities including thinking and planning skills, and promote enjoyment.